Mechanical properties of alumina/zirconia composites. Issue 1 (January 2020) - Boniecki, Marek; Sadowski, Tomasz; Gołębiewski, Przemysław; Węglarz, Helena; Piątkowska, Anna; Romaniec, Magdalena; Krzyżak, Konrad; Łosiewicz, Kamil
Abstract: Fracture toughness, bending strength, Young's modulus, hardness and subcritical crack growth were determined for six different alumina/zirconia composites. The bending strength was modelled using Weibull distribution. The fracture toughness, bending strength and resistance to subcritical crack growth increase as a function of ZrO2 content (stabilized with 3 mol% Y2 O3 ). The authors claim that a threshold stress in a three-parameter Weibull distribution may correspond to a threshold stress intensity factor in which the subcritical crack growth is negligible.